Using Zebrafish for Investigating the Molecular Mechanisms of Drug-Induced Cardiotoxicity. (27th September 2018) - Zakaria, Zain Z.; Benslimane, Fatiha M.; Nasrallah, Gheyath K.; Shurbaji, Samar; Younes, Nadin N.; Mraiche, Fatima; Da'as, Sahar I.; Yalcin, Huseyin C.
Abstract : Over the last decade, the zebrafish ( Danio rerio ) has emerged as a model organism for cardiovascular research. Zebrafish have several advantages over mammalian models. For instance, the experimental cost of using zebrafish is comparatively low; the embryos are transparent, develop externally, and have high fecundity making them suitable for large-scale genetic screening. More recently, zebrafish embryos have been used for the screening of a variety of toxic agents, particularly for cardiotoxicity testing. Zebrafish has been shown to exhibit physiological responses that are similar to mammals after exposure to medicinal drugs including xenobiotics, hormones, cancer drugs, and also environmental pollutants, including pesticides and heavy metals. In this review, we provided a summary for recent studies that have used zebrafish to investigate the molecular mechanisms of drug-induced cardiotoxicity. More specifically, we focused on the techniques that were exploited by us and others for cardiovascular toxicity assessment and described several microscopic imaging and analysis protocols that are being used for the estimation of a variety of cardiac hemodynamic parameters.